2021
DOI: 10.1063/5.0051047
|View full text |Cite
|
Sign up to set email alerts
|

Dominating migration barrier for intrinsic defects in gallium oxide: Dose-rate effect measurements

Abstract: Ion bombardment provides an opportunity to study basic properties of intrinsic defects in materials since the radiation-induced disorder accumulation depends on the balance between defect generation and migration rates. In particular, variation of such parameters as irradiation temperature and ion flux, known in the literature as dose-rate effect, interconnects the macroscopically measured lattice disorder with the migration barrier of the dominating defects. In this work, we measured the dose-rate effect in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…VGa for the present case. Neglecting the binding energy and accounting for the recently reported VGa migration energy of ~0.8 eV [23], from the data in Fig. 3(c) the upper limit of the VGa formation energy can be estimated as ~2.4 or ~4.6…”
Section: Please Cite This Article As Doi: 101063/50070045mentioning
confidence: 96%
“…VGa for the present case. Neglecting the binding energy and accounting for the recently reported VGa migration energy of ~0.8 eV [23], from the data in Fig. 3(c) the upper limit of the VGa formation energy can be estimated as ~2.4 or ~4.6…”
Section: Please Cite This Article As Doi: 101063/50070045mentioning
confidence: 96%
“…For example, Ander et al have detected κ phase in the β-Ga 2 O 3 matrix upon heavy ion implants [7], even though the evolution of this process as a function of the implantation parameters has not been explored. More recently, interesting strain accumulation was observed in ion implanted α-Ga 2 O 3 [8] and β-Ga 2 O 3 [9]. However, the systematic understanding of the disorder-induced ordering in Ga 2 O 3 polymorphs was missing in literature.…”
mentioning
confidence: 99%
“…Previously, it was demonstrated that surface amorphization in ion implanted GaN exhibits threshold-like behavior that was explained in the framework of the energy spike models 20 . However, in contrast to GaN, no amorphization was observed in ion implanted β-Ga 2 O 3 5 , 7 and the disorder enhancement in β-Ga 2 O 3 for cluster ions can be attributed to a nonlinear defect interaction as supported by a strong dose-rate effect in this material 13 .
Figure 3 Amplitudes of the surface disorder peak in the ion implanted β-Ga 2 O 3 (deduced from the spectra shown in Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…In context of the literature interpretations of the XRD data in irradiated materials, such shoulders/peaks may be attributed to the accumulation of compressive strain 21 . Previously, we demonstrated that this strain accumulation is scaling with the disorder level in the bulk damage peak 13 . However, surprisingly enough, the strain value does not scale up with the enhanced disorder in samples implanted with the cluster ions.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation